Key factors affecting photoelectrochemical performance of g-C3N4 polymer films. Issue 50 (5th June 2019) - Ruan, Qiushi; Bayazit, Mustafa K.; Kiran, Vankayala; Xie, Jijia; Wang, Yiou; Tang, Junwang
Abstract : The charge diffusion length of the g-C3 N4 film was found to be ∼1000 nm, indicating the maximum thickness of an efficient g-C3 N4 photoelectrode. Abstract : We investigated the relationship between crystallinity, deep trap states and PEC performance of g-C3 N4 photoelectrodes. Long-lived charge carriers were present in the more poorly crystalline samples, due to deeper trap states, which inversely correlated with photoelectrochemical performance. The charge diffusion length in a compact g-C3 N4 film was determined to be ca. 1000 nm.